Utilização de fungos endofíticos no controle de pragas agrícolas: uma revisão - Almeida, Thiago Kaziski de (Universidade Federal de São Carlos, 2025)
This study presents a comprehensive analysis of the use of endophytic fungi in the biological control of agricultural pests, addressing biological mechanisms, plant–microorganism interactions, practical applications, and the agronomic potential of this technology. Based on an extensive literature review, ecological, metabolic, and physiological aspects related to the role of endophytes in plant defense were examined, emphasizing their contribution to integrated pest management, the reduction of chemical pesticide use, and the advancement of sustainable agricultural systems. The findings reveal that these microorganisms act through multiple and complementary pathways, such as antibiosis, competition, systemic resistance induction, and hormonal modulation, resulting in continuous and multifunctional protection. Operational challenges, environmental limitations, inoculation requirements, and field colonization variables were also evaluated. Overall, the review demonstrates that endophytic fungi represent a highly promising and strategic alternative for modern agriculture, offering biologically efficient solutions aligned with contemporary economic and environmental demands. The study concludes that strengthening research, standardizing protocols, and improving commercial formulations will be essential for the large-scale consolidation of this biotechnology.
Use of endophytic fungi on agricultural pest control: a review
Keywords: Fungos endofíticos; Biocontrole; Agricultura sustentável; Manejo integrado de pragas; Microbiologia agrícola; Agricultural microbiology; Biocontrol; Endophytic fungi; Integrated pest management; Sustainable agriculture; CIENCIAS AGRARIAS::AGRONOMIA; 2. Fome Zero e Agricultura Sustentável